Koala: Ultra-Low Power Data Retrieval in Wireless Sensor Networks - Musaloiu-E, Razvan; Liang, Chieh-Jan Mike; Terzis, Andreas (IPSN (International Conference on Information Processing in Sensor Networks), 2008)
We present Koala, a reliable data retrieval system designed to operate at permille (.1%) duty cycles, essential for long term environmental monitoring networks. Koala achieves these low duty cycles by letting the network's nodes sleep most of the time and reviving them through an efficient wake-up strategy whenever the gateway performs a bulk data download. Unlike other systems which consume energy to maintain consistent network state (e.g. routes, sleep schedules, etc.) across the network's nodes, Koala maintains no persistent routing state on the motes. Instead, a basestation calculates the network paths using reachability information collected by the motes. The Flexible Control Protocol (FCP), a protocol we developed, is then used to install this routing information on the network's nodes. This paradigm of operation not only eliminates the overhead of maintaining routing state, but also significantly reduces the complexity of the networking code running on the motes. Results from simulation and an actual implementation on TinyOS 2 indicate that Koala can achieve very low duty cycles under a wide range of download and network sizes.